2011
DOI: 10.1097/cej.0b013e328348fc21
|View full text |Cite
|
Sign up to set email alerts
|

The maternal womb

Abstract: The dramatic rise in worldwide prevalence of obesity has necessitated the search for more efficacious anti-obesity strategies to counter the increased cancer risks in overweight and obese individuals. The mechanistic pathways linking obesity status with adult chronic diseases such as cancer remain incompletely understood. A growing body of evidence suggests that novel approaches and interventional agents to disrupt the feed-forward cycle of maternal to offspring obesity transfer that is initiated in utero, wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 147 publications
0
10
0
Order By: Relevance
“…Consequently, though pre-pregnancy and gestational diabetes both result in maternal hyperglycemia, their impact on fetal development is dependent on the management of these conditions [51]. Maternal hyperglycemia increases fetal growth, alters fetal metabolism, and induces oxidative stress and epigenetic changes [28, 52, 53]. The pathways linking maternal diabetes to childhood cancer risk are not fully understood, but the associations we observed are likely explained by a combination of these factors, which may explain why we did not find a consistently higher risk for all childhood cancers that have been associated with accelerated fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, though pre-pregnancy and gestational diabetes both result in maternal hyperglycemia, their impact on fetal development is dependent on the management of these conditions [51]. Maternal hyperglycemia increases fetal growth, alters fetal metabolism, and induces oxidative stress and epigenetic changes [28, 52, 53]. The pathways linking maternal diabetes to childhood cancer risk are not fully understood, but the associations we observed are likely explained by a combination of these factors, which may explain why we did not find a consistently higher risk for all childhood cancers that have been associated with accelerated fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in mouse models have demonstrated causality between maternal obesity and offspring’s compromised cardiovascular health and increased cancer risks (Blackmore HL et al , 2014; Simmen & Simmen, 2011). While consumption of a high-fat diet does not necessarily result in obesity, there is a growing consensus that maternal dietary intake of high-fat mimicking a typical ‘Western diet’, similar to maternal obesity, elicits metabolic dysfunctions in progeny through early changes in metabolome due in part to deregulated insulin signaling (Cox et al , 2009; Montales et al , 2014; Vogt et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increasing evidence supports a possible link between metabolic syndrome and breast cancer (Simmen & Simmen, 2011; Hauner & Hauner, 2014). A recent study from our group (Montales et al , 2014) provided a proof of this concept by using the Wnt1-Transgenic (Tg) mouse model of human breast cancer (Li et al , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…All the current data suggest that maternal obesity is linked to other cancer outcomes through secondary mechanisms. For example, a recent review proposed that maternal obesity influences obesity and weight gain in offspring and therefore predisposes offspring to colorectal cancer (30). This is founded on the observation that obesity of the patient at diagnosis and weight gain in adult life are risk factors for colorectal cancer (30).…”
Section: In Utero and Early-life Exposuresmentioning
confidence: 99%